Micro-credential: i’ve aced the interview…what’s next? / Sarah Sabir Ahmad and Azfahanee Zakaria - Ahmad, Sarah Sabir; Zakaria, Azfahanee (Universiti Teknologi MARA, Kedah, 2023)
Starting a new job can be both exciting and challenging for individuals. According to the Society for Human Resource Management (SHRM), 31% of new hires leave their jobs within the first six months. Adapting to a new work environment, building relationships with colleagues, managing expectations and continuous learning are among the challenges faced by individuals when starting a new job. Therefore, this micro-credential (MC) examines the issues that individuals commonly face when embarking on a new job and explores potential strategies to overcome these challenges. It highlights the importance of adapting to a new work environment, building relationships with colleagues, managing expectations, and developing a strong foundation for long-term success. This MC also discusses the significance of effective communication, continuous learning, and maintaining a positive mindset during the transitional period. By addressing these issues proactively, individuals can navigate the initial challenges of a new job and establish a solid foundation for professional growth and career advancement.